2016
DOI: 10.21062/ujep/x.2016/a/1213-2489/mt/16/1/295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shot Peening on the Fatigue Properties of 40NiCrMo7 steel

Abstract: Fatigue properties of 40NiCrMo7 low alloy steel in the high cycle region were tested by rotating bending fatigue loading (f = 40 Hz, T = 20 5 , R = -1) on notched specimens after application of shot peening surface treatment (cast steel balls with diameter of 0.43 mm, Almen intensity 12A, coverage 100 % and consequently the surface was re-peened with glass beads to decrease the final roughness). The compressive residual stresses created by shot peening increased the time necessary for fatigue crack initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Application of the ultrasonic impact peening led to an increase in fatigue strength, in the case of the N = 10 5 loading cycles by 6.3 %; in the case of the N = 10 7 loading cycles by 12.6 % ( Table 2). These facts are in accordance with works [8][9][10][11][12][13][14][15], where the values within 20 % are reported. The positive result of increased fatigue strength is the surface layer strengthening by the cold plastic deformation.…”
Section:   supporting
confidence: 93%
See 1 more Smart Citation
“…Application of the ultrasonic impact peening led to an increase in fatigue strength, in the case of the N = 10 5 loading cycles by 6.3 %; in the case of the N = 10 7 loading cycles by 12.6 % ( Table 2). These facts are in accordance with works [8][9][10][11][12][13][14][15], where the values within 20 % are reported. The positive result of increased fatigue strength is the surface layer strengthening by the cold plastic deformation.…”
Section:   supporting
confidence: 93%
“…In addition, the grain boundaries are often sources of dislocations, sites of exclusion of the admixture elements and secondary phases. The results are increases in the yield strength, ultimate strength limit and hardness [7,[8][9][10][11][12][13][14][15][16]. The fatigue safety coefficients k u , Table 3, Fig.3 to 6, were calculated by the four methods (Goodman, Gerber, ASME and Soderberg).…”
Section:   mentioning
confidence: 99%
“…In the shot peening process, thousands of balls impact the surface of target material, which causes plastic deformation and subsequently induces compressive stresses in the subsurface [1][2][3][4]. After being shot peened, the surface layers of the target material become harder and rougher than its surrounding unaffected surface area [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Shot peening process can significantly improve the fatigue strength of engineering components [7]. Hassani-Gangaraj et al [59], Voorwald et al [74], and Závodská et al [109] have described shot peening as a viable method to introduce the compressive residual stresses to retard the crack propagation in the material but, Bagherifard et al [58] indicated that the high surface roughness, which occurs during the peening process, has a deterimental effect in reducing the fatigue life of the shot peened steel. Hence a secondary polishing step is recommended to decrease the surface roughness of the treated samples: these could be prolonging the treatment time, removing a thin layer of material (abrasive grinding and electropolishing), or re-shot peening.…”
Section: Introductionmentioning
confidence: 99%